TOURISM AS A TOOL FOR THE CONSERVATION OF THE SOUTHERN ELEPHANT SEAL (MIROUNGA LEONINA) AND ITS HABITATS IN TIERRA DEL FUEGO, CAPE HORN BIOSPHERE RESERVE, CHILE - Kirk, Christian; Rozzi Marin, Ricardo Roberto; Gelcich, Stefan (My University, 2018)
The southern elephant seal (Mirounga leonina Linnaeus 1758) is a rare species on the Chilean coast outside the Chilean Antarctic territory. In Tierra del Fuego, stable and reproductive colonies of this species have been identified, and it has been described as the first marine mammal to be used in the tourism industry in the Magellanic and Antarctic Region of Chile In order to establish the importance that the conservation of this species and its habitats has for tourists, 355 surveys were carried out on cruise ship passengers that visiting the Almirantazgo sound and other areas of the Darwin Cordillera in the Cape Horn Biosphere Reserve. Surveys assessed the profile of tourists who visit this reserve with the company Cruceros Australis, considering their knowledge about nature conservation and their willingness to collaborate in a program for the conservation of the elephant seal, that habitats and biodiversity of the Chilean Patagonia. More than 76% of the respondents showed a willingness to contribute to a conservation program of this species and the biodiversity of Patagonia. Among the respondents, 53% were willing to contribute US $100 or 200. Considering a number of 14 thousand tourists who embarked on Crucerso Australis in 2012, the total contribution per year could be greater than US $1,000,000. This result that identifies a high potential contribution by tourists is consistent with the records for other regions of the world, where a well-preserved protected area (such as the Cape Horn Biosphere Reserve) has the potential to generate greater contributions with lower number of tourists than a protected area with massive numbers of tourists and conservation problems, as it has been the case of the Torres del Paine Biosphere Reserve during the last two decades.
Keywords: biodiversity; marine mammals; protected areas; sustainable tourism; willingness to pay